MANAGEMENT OF STUDENT DEVELOPMENT IN THE DEVELOPMENT OF NON ACADEMIC ACHIEVEMENT IN SENIOR HIGH SCHOOL - Ramadhan, Aqsal Rizky; Sujarwo, Sujarwo; Khamid, Muh (JURNAL EDUSCIENCE, 2025)
Purpose-The importance of managing student development to develop non-academic achievements, which are often less noticed than academic achievements. The increasing demands of society for diverse skills, good management of student development becomes an urgent need to support students' potential optimally. This study aims to analyze the management of student development in the development of non-academic achievement, including planning, organizing, actuating, and controlling.Methodology-The method used in this study was a qualitative case study. This research was conducted at Senior High School 4 Yogyakarta and Senior High School 1 Sewon, Yogyakarta Special Region Province. Sampling in this study uses a purposive sampling technique and the subjects of this study were the principal, vice principal for student affairs, and extracurricular coordinator teachers. The data collection technique used interviews, observation, and document studies.Findings-The findings of this study are the management of student development in the development of non-academic achievement at Senior High School 4 Yogyakarta and Senior High School 1 Sewon included: (a) Planning, starting with mapping students' interests and talents through surveys and school orientation, resulting in extracurricular and competition programs. (b) Organizing, carried out effectively with clear task divisions. (c) Implementing extracurricular activities in a structured manner tailored to the objectives of fields such as arts, sports, science, and leadership. (d) Strict supervision through attendance, digital documentation, and evaluation of results.Significance-In addition, this approach serves as a reference for taking strategic and proportional steps to ensure that high school students can develop their non-academic achievements.Keywords: Management; Student development; Non-academic achievement